Otolith Growth Ring Pattern of Hampala macrolepidota Kuhl and Van Hasselt, (1823) from the Kampar Kiri River, Mentulik Village , Kampar Kiri Hilir District, Riau Province - Situmorang, Tety E; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK Kampar Kiri River is one of the rivers that are polluted due to human activities along the river. Decrement of water quality may affect the growth of fish and it is reflected on the pattern of otolith growth rings. A research aims to understand the pattern of otolith growth rings in the H. macrolepidota was conducted in January to March 2018. Sampling was done four times for two months. The fish was captured using a gill net. There were 52 fishes (10 females and 42 males) captured. The otolith (sagita) were removed and shaved. Results shown that the otolith length was 0.75 to 6 mm and their weight was 0.0008 to 0.02 g. There were dark and light rings in the otolith. Twenty six fishes had dark rings (1-3 rings/fish). Distance between the nucleus and the first dark ring was 0.02 to 0.5 mm. These data indicates that the formation of the dark ring may not be affected by periodical condition such as season or periodic physiological condition such as reproductive activities. The formation of dark ring in the otolith seem to be individual and not concurrent in fish population. Water quality in the sampling area was good (temperature 26 to 27⁰C; pH 5; DO 2.2 to 3.9 mg/L; and CO2 9.9 to 15.9 mg/L) and it may be sufficient to support the life of the fish. Keywords: Polluted water, dark ring, relative growth, sagita